The invention of hypoxia - Richalet, J. P. (Journal of Applied Physiology, 2021)
The word "hypoxia" has recently come to the attention of the general public on two occasions, the Nobel Prize in Medicine or Physiology in 2019 and the recent COVID-19 pandemic. In the academic environment, hypoxia is a current topic of research in biology, physiology, and medicine: in October 2020, there were more than 150,000 occurrences of "hypoxia" in the PubMed database. However, the first occurrence is dated to 1945, while the interest for the effects of oxygen lack on the living organisms started in the mid-19th century, when scientists explored high altitude regions and mainly used the terms "anoxia" or "anoxemia." I therefore researched online through multiple databases to look for the first appearance of "hypoxia" and related terms "hypoxemia" and "hypoxybiosis" in scientific literature published in English, German, French, Italian, and Spanish. Viault and Jolyet used "Hypohématose" in 1894, but this term has not been used since. Hypoxybiosis first appeared in 1909 in Germany, then hypoxemia in 1923 in Austria, and hypoxia in 1938 in Holland. It was then exported to the United States where it appeared in 1940 in cardiology and anesthesiology. The clinical distinction between anoxia and hypoxia was clearly defined by Carl Wiggers in 1941. Hypoxia (decrease in oxygen), by essence variable in time and in localization in the body, in contrast with anoxia (absence of oxygen), illustrates the concept of homeodynamics that defines a living organism as a complex system in permanent instability, exposed to environmental and internal perturbations.